2016
DOI: 10.3109/10903127.2015.1111477
|View full text |Cite
|
Sign up to set email alerts
|

Unnecessary Use of Red Lights and Sirens in Pediatric Transport

Abstract: Introduction Approximately 25.5 million pediatric patients are treated in Emergency Departments around the United States annually. Roughly 7% of these patients are transported by ambulance; of these, about 7% arrive in ambulances running red lights and sirens (RLS). Compared to those transporting without RLS, emergency vehicles employing RLS are involved in more accidents and are associated with more fatalities. Objective To characterize the use of RLS in pediatric transports and identify factors associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Overall, the CSI-EMS is a study with several components that have been described elsewhere. 814 This portion of the study consisted of a medical records review of lights and sirens (“Code 3”) pediatric transports from an urban county in Oregon. The study was approved by the IRB of Oregon Health & Science University.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the CSI-EMS is a study with several components that have been described elsewhere. 814 This portion of the study consisted of a medical records review of lights and sirens (“Code 3”) pediatric transports from an urban county in Oregon. The study was approved by the IRB of Oregon Health & Science University.…”
Section: Methodsmentioning
confidence: 99%
“…Paramedics’ ability to predict hospital admission and the aetiology of the condition in adults has been shown to be moderate in several studies [3537]. In one study, 19% of the paediatric transports with lights and sirens were later identified as unnecessary [38]. In a study of adults from Ireland, advanced paramedics showed agreement in 70% of the cases when the field diagnosis and the ED physicians’ working diagnosis were compared.…”
Section: Discussionmentioning
confidence: 99%
“…For pediatrics, the transport destination determined by the EMS clinician is a particularly important aspect of the child's overall emergency care. If a child is transported to a hospital that is not capable of providing definitive care, they must undergo interfacility transport (IFT) to another facility ("secondary transport") which both prolongs care and is associated with patient harms [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%